Direct Photomodification of Polymer Surfaces: Unleashing the Potential of Aryl‐Azide Copolymers. (27th May 2018) - Schulz, Anita; Stocco, Antonio; Bethry, Audrey; Lavigne, Jean‐Philippe; Coudane, Jean; Nottelet, Benjamin
Abstract: The possibility to impart surface properties to any polymeric substrate using a fast, reproducible, and industrially friendly procedure, without the need for surface pretreatment, is highly sought after. This is in particular true in the frame of antibacterial surfaces to hinder the threat of biofilm formation. In this study, the potential of aryl‐azide polymers for photofunctionalization and the importance of the polymer structure for an efficient grafting are demonstrated. The strategy is illustrated with a UV‐reactive hydrophilic poly(2‐oxazoline) based copolymer, which can be photografted onto any polymer substrate that contains carbon–hydrogen bonds to introduce antifouling properties. Through detailed characterization it is demonstrated that the controlled spatial distribution of the UV‐reactive aryl‐azide moieties within the poly(2‐oxazline) structure, in the form of pseudogradient copolymers, ensures higher grafting efficacy than other copolymer structures including block copolymers. Furthermore, it is found that the photografting results in a covalently bound layer, which is thermally stable and causes a significant antiadherence effect and biofilm reduction against Escherichia coli and Staphylococcus epidermidis strains while remaining noncytotoxic against mouse fibroblasts. Abstract : Photoinsertion of rationally designed aryl‐azide copolymers is exploited for an efficient and direct surface modification of polymer surfaces. The photografting efficiency is discussed with respect to the macromolecular structures with a pseudogradient copolymer giving highest efficacy. The versatility of the approach is illustrated with antifouling poly(2‐oxazoline)‐based copolymers to impart antibacterial properties to various clinically relevant polymer substrates.